Beginning Web Programming With Html, Xhtml And Css - Jon Duckett (Wrox beginning guides, 2008)
This book teaches people how to write web pages using HTML, XHTML, and CSS. It shows the reader how to make their pages work in several generations of Web browsers, including Web-enabled devises such as mobile phones. It covers the most commonly used programming/scripting language - JavaScript and provide readers with a roadmap of other web technologies to learn after mastering this book to add more functionality to their sites.